A method for restoring the ionic conductivity of a sulfide-based solid electrolyte, a sulfide-based solid electrolyte whose ionic conductivity has been restored by this method, and a lithium-ion secondary battery containing this solid electrolyte.

By treating sulfide-based solid electrolytes with a solvent of low dielectric constant and drying, the method restores ionic conductivity, enhancing the performance of lithium ion secondary batteries.

JP2025500991AActive Publication Date: 2025-01-15LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024539055
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-13
Filing Date
2023-06-15
Publication Date
2025-01-15
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

Sulfide-based solid electrolytes suffer from significant decreases in ionic conductivity due to moisture exposure, which affects the performance of all-solid-state batteries.

Method used

Contacting sulfide-based solid electrolytes with a solvent having a dielectric constant of less than 7 and then drying the electrolyte to restore ionic conductivity.

Benefits of technology

The method effectively recovers ionic conductivity in sulfide-based solid electrolytes, improving the performance of lithium ion secondary batteries by maintaining high conductivity levels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500991000001_ABST
    Figure 2025500991000001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for restoring the ionic conductivity of a sulfide-based solid electrolyte, the method comprising the steps of: a) bringing a sulfide-based solid electrolyte whose ionic conductivity has decreased into contact with a solvent having a dielectric constant of less than 7; and b) drying the solid electrolyte that has been in contact with the solvent; a sulfide-based solid electrolyte whose ionic conductivity has been restored by this method; and a lithium ion secondary battery including this solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0077323 filed on June 24, 2022 and Korean Patent Application No. 10-2023-0075819 filed on June 13, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a method for restoring the ionic conductivity of a sulfide-based solid electrolyte, a sulfide-based solid electrolyte whose ionic conductivity has been restored by this method, and a lithium ion secondary battery including this solid electrolyte. [Background technology]

[0003] Lithium ion secondary batteries have a high energy density and are therefore used in a variety of applications, such as electric automobiles and portable information terminals.

[0004] Most conventional lithium-ion secondary batteries use liquid electrolytes such as organic solvents, but there have been constant safety concerns about electrolyte leakage and the associated risk of fire, etc. For this reason, interest has recently been growing in all-solid-state batteries that use inorganic solid electrolytes.

[0005] All-solid-state batteries are based on technology that does not use organic solvents (liquid electrolytes), and have the advantage that battery cells can be manufactured safely and simply. To improve the performance of such all-solid-state batteries, solid electrolytes with high ion conductivity and safety are required, and related research is being actively conducted for this reason.

[0006] The sulfide-based solid electrolyte has a lithium ion transport number of about 1 and an ionic conductivity of about 10 -3S / cm, they are attracting attention as solid electrolytes that contribute to improving battery characteristics. Sulfide-based solid electrolytes are manufactured by methods such as the melt quenching method and the solid phase reaction method.

[0007] However, sulfide-based solid electrolytes easily react with moisture, and even a small amount of moisture can cause their shape and properties to change. For example, sulfide-based solid electrolytes react with moisture in the air to generate hydrogen sulfide (H2S) gas, which significantly reduces the ionic conductivity. Specifically, when a sulfide-based solid electrolyte is exposed to a dry room environment for about five hours, the ionic conductivity decreases by 20 to 60%.

[0008] The ionic conductivity of a solid electrolyte has an important effect on the performance of a secondary battery to which the solid electrolyte is applied, and therefore the ionic conductivity of the solid electrolyte is used as an index value for evaluating the performance of the secondary battery.

[0009] Therefore, in order to improve the performance of secondary batteries, there is a need to develop not only a technology for producing a solid electrolyte with high ionic conductivity, but also a technology for stably maintaining and recovering the ionic conductivity of the produced solid electrolyte. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Japanese Patent Publication No. 2015-018726 Summary of the Invention [Problem to be solved by the invention]

[0011] The present inventors conducted extensive research into a method for restoring the ionic conductivity of a sulfide-based solid electrolyte whose ionic conductivity has been reduced by an external environment, and discovered that when a sulfide-based solid electrolyte whose ionic conductivity has been reduced is treated with a specific solvent, the ionic conductivity is restored, thereby completing the present invention.

[0012] Therefore, an object of the present invention is to provide a method for restoring the ionic conductivity of a sulfide-based solid electrolyte, a sulfide-based solid electrolyte whose ionic conductivity has been restored by this method, and a lithium-ion secondary battery including this solid electrolyte. [Means for solving the problem]

[0013] In order to achieve the above object, the present invention provides a) contacting the sulfide-based solid electrolyte having reduced ionic conductivity with a solvent having a dielectric constant of less than 7; and b) drying the solid electrolyte that has been in contact with the solvent.

[0014] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: The method of the present invention provides a sulfide-based solid electrolyte having restored ionic conductivity.

[0015] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: a positive electrode; a negative electrode; and a solid electrolyte interposed between the positive electrode and the negative electrode; The solid electrolyte provides a lithium ion secondary battery containing the solid electrolyte of the present invention. Effect of the Invention

[0016] The method for restoring the ionic conductivity of a sulfide-based solid electrolyte of the present invention provides the effect of efficiently restoring the ionic conductivity of the solid electrolyte by a simple treatment.

[0017] In addition, the method for restoring ionic conductivity and the sulfide-based solid electrolyte whose ionic conductivity has been restored by the method make it possible to use a solid electrolyte having high ionic conductivity when assembling a battery.

[0018] Furthermore, the lithium ion secondary battery of the present invention contains the above-mentioned solid electrolyte, thereby providing the effect of improving the performance of the battery. [Brief description of the drawings]

[0019] [Figure 1] 2 is a graph showing the ionic conductivity of solid electrolytes prepared in a control example, a comparative example, and an example of the present invention; MODE FOR CARRYING OUT THEINVENTION

[0020] The present invention will now be described in further detail.

[0021] The method for recovering the ionic conductivity of a sulfide-based solid electrolyte of the present invention comprises the steps of: a) contacting the sulfide-based solid electrolyte having reduced ionic conductivity with a solvent having a dielectric constant of less than 7; and b) drying the solid electrolyte that has been in contact with the solvent.

[0022] In one embodiment of the present invention, the decrease in ionic conductivity in step a) may be due to exposure of the sulfide-based solid electrolyte to moisture, and the moisture exposure may be due to contact with moisture, exposure to air containing moisture, or the like.

[0023] In one embodiment of the present invention, the decrease in ionic conductivity in step a) may be a decrease in ionic conductivity of 1 to 80%, 6 to 80%, 1 to 70%, or 6 to 70% based on the ionic conductivity of the sulfide-based solid electrolyte before exposure to the atmosphere being 100%, or may be a decrease in ionic conductivity of 6 to 60%, 10 to 60%, 20 to 60%, or 30 to 50%.

[0024] In one embodiment of the present invention, the recovery of ionic conductivity in the step a) may be an increase in the ionic conductivity of the sulfide-based solid electrolyte having a decreased ionic conductivity by a range consisting of a lower limit selected from 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 25%, 30%, 35%, and 40%, and an upper limit selected from 300%, 250%, 200%, 150%, 100%, 80%, 60%, and 40%. For example, the increase may be 1 to 300% or 10 to 300%. The ionic conductivity of the sulfide-based solid electrolyte having a reduced ionic conductivity may be increased to 50 to 100%, 50 to 98%, 50 to 95%, 70 to 95%, 80 to 95%, 80 to 94%, or 85 to 94% based on the ionic conductivity of the sulfide-based solid electrolyte before the reduction in ionic conductivity being 100%.

[0025] Examples of the solvent having a dielectric constant of less than 7 include xylene, isobutyl butyrate, anisole, toluene, hexane, heptane, isobutyl isobutyrate (IBIB), decane, dibutyl ether, butyl bytyrate, etc., which may be used alone or in combination of two or more. In the above, xylene may be ortho-, meta-, or para-xylene.

[0026] In particular, one or more solvents selected from the group consisting of xylene, isobutyl butyrate, and anisole may be more preferably used.

[0027] The solvent used may more preferably have a dielectric constant of 1 to 5.

[0028] The solvent must be non-reactive with the solid electrolyte, and therefore a non-polar or weakly polar solvent may be used. Specifically, a solvent having a dipole moment of 5D or less may be used.

[0029] The method for recovering the ionic conductivity of a sulfide-based solid electrolyte according to the present invention can be applied to a solid electrolyte in a particulate (powder) state.

[0030] Sulfide-based solid electrolytes have a lithium ion transport number of about 1 and an ionic conductivity of about 10 -3 Because of its low molecular weight (S / cm), it is attracting attention as a solid electrolyte that contributes to improving battery characteristics.

[0031] However, sulfide-based solid electrolytes react easily with moisture, and even a small amount of moisture can cause changes in shape and properties, resulting in a significant decrease in ionic conductivity. Specifically, when a sulfide-based solid electrolyte is exposed to a dry room environment (H2O 100-160 ppm) for five hours, its ionic conductivity decreases by 20-60%.

[0032] In the manufacturing process of an all-solid-state or semi-solid-state battery, a sulfide-based solid electrolyte may be used for battery assembly immediately after manufacturing, but is generally used for battery assembly after a storage process. Therefore, if an all-solid-state or semi-solid battery is manufactured using a sulfide-based solid electrolyte whose ion conductivity has decreased during storage, this can cause a decrease in the performance of the battery.

[0033] The present invention is characterized by providing a solution that can efficiently solve the above problems.

[0034] In one embodiment of the present invention, the contact between the sulfide-based solid electrolyte and the solvent can be carried out by various methods known in the art, such as by mixing the solid electrolyte with the solvent, spraying the solvent onto the solid electrolyte, or immersing the solid electrolyte in the solvent.

[0035] It may be preferable in some cases that the contact between the sulfide-based solid electrolyte and the solvent is carried out so that the entire surface of the sulfide-based solid electrolyte is wetted with the solvent.

[0036] The mixing may be carried out for generally 1 minute or more, preferably 1 minute to 1 hour, and more preferably 1 minute to 10 minutes. However, as the amount of solid electrolyte to be treated increases, the treatment time increases proportionately, and therefore the time is not limited to the above.

[0037] In one embodiment of the present invention, the mixing is preferably carried out by stirring the mixture, and the stirring may be carried out, for example, in the range of 100 rpm to 3000 rpm, preferably 1000 rpm to 2000 rpm.

[0038] In one embodiment of the present invention, the drying is preferably carried out under a vacuum atmosphere.

[0039] The drying method is not particularly limited, but may be preferably performed under heated conditions, for example. In this case, the drying temperature may be, for example, 25 to 100°C, more preferably 45 to 70°C.

[0040] In one embodiment of the present invention, the cause of the decrease in ionic conductivity of the sulfide-based solid electrolyte is not particularly limited, but may be, for example, due to exposure of the sulfide-based solid electrolyte to moisture, and the moisture exposure may be moisture exposure due to contact with moisture, exposure to air containing moisture, or the like.

[0041] The present invention can be preferably applied to a case where the ionic conductivity of a sulfide-based solid electrolyte is reduced due to contact with the air containing moisture after production.

[0042] In one embodiment of the present invention, the sulfide-based solid electrolyte is, but is not limited to, for example, Li 10 GeP2S 12 , Li2S-P2S5 glass, thio-LISICONS, Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 , Li6PS5X (LPSX; X = Cl, Br, I) argyrodites, Li 12-m-x+ (M m+ Y4 2- )Y 2-x 2- X x - (wherein M=Si, Ge, Sn, P, As; Y=O, S, Se, Te; X=Cl, Br, I; 0≦x≦2) and the like. However, the present invention is not limited to these, and any sulfide-based solid electrolyte can be used without any particular limitation.

[0043] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: The present invention relates to a sulfide-based solid electrolyte whose ionic conductivity has been restored by the method of the present invention.

[0044] The sulfide-based solid electrolyte is a) contacting the sulfide-based solid electrolyte having reduced ionic conductivity with one or more solvents consisting of xylene, isobutyl butyrate, and anisole; and b) drying the solid electrolyte that has been in contact with the solvent.

[0045] The above-mentioned manufacturing method can be applied to the manufacturing method, and therefore the same description will be omitted.

[0046] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: a positive electrode; a negative electrode; and a solid electrolyte interposed between the positive electrode and the negative electrode; The solid electrolyte provides a lithium ion secondary battery containing the sulfide-based solid electrolyte of the present invention.

[0047] The lithium ion secondary battery may be an all-solid-state or semi-solid-state battery.

[0048] The technical contents related to the present invention will be described below with specific examples.

[0049] Sulfide solid electrolyte The sulfide-based solid electrolyte according to the present invention may include sulfide-based solid electrolyte particles treated with a solvent as described above, and the particles may be processed into a film-like sulfide-based solid electrolyte by a dry or wet process.

[0050] The sulfide-based solid electrolyte may include a mixture in which binder particles are dry-mixed with the sulfide-based solid electrolyte particles.

[0051] The sulfide-based solid electrolyte may be prepared by coating a slurry containing the sulfide-based solid electrolyte particles, a binder, and a solvent on a substrate and drying the slurry.

[0052] The dry process is a method for producing a solid electrolyte sheet by pressing a solid electrolyte powder, and can be carried out, for example, by stacking a solid electrolyte powder, a positive electrode active material powder, and a negative electrode active material powder, and pressing them to produce a cell.

[0053] The solid electrolyte powder may further include a binder powder. Examples of the binder powder used in the dry process include, but are not limited to, PTFE.

[0054] In the above, the binder powder may be included in an amount of 1 to 5 parts by weight based on 100 parts by weight of the solid electrolyte powder.

[0055] The wet process is a method for producing a solid electrolyte sheet by coating a substrate with a slurry containing a solvent, a binder, and a solid electrolyte powder.

[0056] According to a preferred embodiment of the present invention, the solid electrolyte slurry may contain 40 to 70% by weight of the solid electrolyte, 1 to 5% by weight of the binder, and 20 to 59% by weight of the solvent.

[0057] The binder may be, but is not limited to, acrylonitrile butadiene rubber (NBR), an acrylic polymer, a silicone polymer, or the like.

[0058] The solvent may be xylene, hexane, benzene, anisole, isobutyl isobutyrate, toluene, or the like, but is not limited thereto.

[0059] The sulfide-based solid electrolyte particles are not particularly limited, and all known sulfide-based solid electrolyte particles used in this field may be used. As the sulfide-based solid electrolyte particles, commercially available ones may be purchased and used, or amorphous sulfide-based solid electrolyte particles may be produced through a crystallization process.

[0060] For example, Li 10 GeP2S 12 , Li2S-P2S5 glass, thio-LISICONS, Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 , Li6PS5X (LPSX; X = Cl, Br, I) argyrodites, Li 12-m-x + (M m+ Y4 2- )Y 2-x 2- X x - (wherein M=Si, Ge, Sn, P, As; Y=O, S, Se, Te; X=Cl, Br, I; 0≦x≦2) and the like. However, the present invention is not limited to these, and any sulfide-based solid electrolyte particles may be used without any particular limitation.

[0061] The average particle size of the sulfide-based solid electrolyte particles may be within the range used in known all-solid or semi-solid batteries, for example, 0.1 μm to 10 μm, and preferably 1 μm to 3 μm. If the average particle size is less than the range, the particles may aggregate, and if it exceeds the range, the porosity of the produced solid electrolyte may be high, the capacity may decrease, and other battery characteristics may be deteriorated, it may be difficult to form a thin film, and it may be disadvantageous in terms of the energy density of the final cell. Preferably, these sulfide-based solid electrolyte particles have an ionic conductivity of 1×10 -3 S / cm or more is preferable, and 5×10 -3 More preferably, it is S / cm or more.

[0062] The sulfide-based solid electrolyte may further include other known solid electrolyte particles in addition to the above-mentioned solid electrolyte particles, for example, an inorganic solid electrolyte or an organic solid electrolyte.

[0063] Examples of the inorganic solid electrolyte include Li2O-B2O3, Li2O-B2O3-P2O5, Li2O-V2O5-SiO2, Li3PO4, Li2O-Li2WO4-B2O3, LiPON, LiBON, Li2O-SiO2, LiI, Li3N, and Li5La3Ta2O. 12 , Li7La3Zr2O 12 , Li6BaLa2Ta2O 12 , LiPO (4-3 / 2w) N W (w is w<1), Li 3.6 S 0.6 P 0.4 O4 etc. may also be used.

[0064] As the organic solid electrolyte, for example, a mixture of a lithium salt with a polymer-based material such as a polyethylene derivative, a polyethylene oxide derivative, a polypropylene oxide derivative, a phosphate polymer, polyagitation lysine, polyester sulfide, polyvinyl alcohol, or polyvinylidene fluoride may be used.

[0065] Manufacturing all-solid-state batteries The all-solid-state battery according to the present invention can be manufactured to have a structure including a positive electrode and a negative electrode with the above-mentioned sulfide-based solid electrolyte disposed therebetween.

[0066] The all-solid-state battery is manufactured, for example, through a dry compression process in which the electrode and the solid electrolyte are prepared in a powder state, then put into a predetermined mold and pressed, or a slurry coating process in which a slurry containing the solid electrolyte, a solvent and a binder is prepared, then coated on the electrode or a release paper, and then dried. The manufacturing method of the all-solid-state battery having the above configuration is not particularly limited in the present invention, and may be carried out by a method known in the art.

[0067] As an example, the all-solid-state battery can be manufactured by disposing a solid electrolyte between a positive electrode and a negative electrode, compressing the resulting cell to assemble it, placing the assembled cell in an exterior material, and then sealing it by heat compression, etc. As the exterior material, a laminate case made of aluminum, stainless steel, etc., a cylindrical or rectangular metal container, or a pouch-type container such as an aluminum pouch may be used.

[0068] The structure, components and manufacturing method of the all-solid-state battery may be applied to any known technology in this field without any restrictions.

[0069] <Positive electrode> The positive electrode of the all-solid-state battery according to the present invention is not particularly limited, and any positive electrode known in the art may be used without limitation. Specifically, a positive electrode in which a positive electrode active material is laminated on a positive electrode current collector may be used.

[0070] The positive electrode current collector may be one that does not cause a chemical change in the battery and has high conductivity, such as stainless steel, aluminum, titanium, baked carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, or the like.

[0071] The positive electrode active material may vary depending on the application of the lithium secondary battery, such as LiNi 0.8-x Co 0.2 Al x O2, LiCo x Mn y O2, LiNi x Co y O2, LiNi x Mn y O2, LiNi x Co y Mn z O2, LiCoO2, LiNiO2, LiMnO2, LiFePO4, LiCoPO4, LiMnPO4, and Li4Ti5O 12 etc. lithium metal oxides (0 < x, y, or z < 1); chalcogenides such as Cu2Mo6S8, FeS, CoS, and NiS; or oxides, sulfides, or halides of scandium, ruthenium, titanium, vanadium, molybdenum, chromium, manganese, iron, cobalt, nickel, copper, zinc, etc. may be used, but are not limited thereto. As the oxide or sulfide, TiS2, ZrS2, RuO2, Co3O4, Mo6S8, V2O5, etc. may be used.

[0072] The shape of the positive electrode active material is not particularly limited, and it may be particulate, for example, spherical, elliptical, rectangular parallelepiped, etc. The average particle diameter of the positive electrode active material may be in the range of 1 to 50 μm, but is not limited thereto.

[0073] The positive electrode may further contain a binder. As the binder, one or more selected from the group consisting of fluorine-containing binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE); polyacrylonitrile (PAN), nitrile butadiene rubber (NBR), styrene butadiene styrene copolymer (SBS), polybutadiene, styrene ethylene butylene styrene copolymer (SEBS), silicone rubber (SR), hydrogenated nitrile butadiene rubber (HNBR), poly(ethylene vinyl acetate) (PEVA), poly(methyl methacrylate) (PMMA), polyisobutene (PIB), etc. may be used. However, it is not limited thereto.

[0074] The content of the binder is not particularly limited as long as it is sufficient to fix the positive electrode active material, and may be, for example, within the range of 0 to 10% by weight based on the entire positive electrode.

[0075] The positive electrode may further include a conductive material, and examples of the conductive material include nickel powder, cobalt oxide, titanium oxide, carbon, etc. Examples of the carbon include at least one selected from the group consisting of ketjen black, acetylene black, furnace black, graphite, carbon fiber, and fullerene.

[0076] The content of the conductive material may be selected in consideration of other battery conditions such as the type of conductive material, and may be, for example, in the range of 1 to 10 wt % based on the total weight of the positive electrode.

[0077] The positive electrode may also further include a sulfide-based solid electrolyte in an amount of about 20% by weight.

[0078] <Negative electrode> The negative electrode of the all-solid-state battery according to the present invention is not particularly limited, and any negative electrode known in the art may be used without limitation. Specifically, lithium metal may be laminated alone on the negative electrode current collector, or a negative electrode active material may be laminated on the negative electrode current collector. Alternatively, only the current collector may be used (anodless), and a protective layer may be applied thereon.

[0079] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the all-solid-state battery and has electrical conductivity. For example, stainless steel, aluminum, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy may be used. In addition, the negative electrode current collector may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., on which fine irregularities are formed, similar to the positive electrode current collector.

[0080] As the negative electrode active material, one or more selected from the group consisting of lithium metal, lithium alloy, lithium metal composite oxide, lithium-containing titanium composite oxide (LTO), and combinations thereof may be used.

[0081] The lithium alloy may be an alloy composed of lithium and at least one metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Ba, Ra, Al, and Sn.

[0082] The lithium metal composite oxide is an oxide (MeO x ) of any one metal selected from the group consisting of lithium and Si, Sn, Zn, Mg, Cd, Ce, Ni, and Fe, and as an example, it may be LixFe2O3 (0 < x ≤ 1) or LixWO2 (0 < x ≤ 1).

[0083] Also, as the negative electrode active material, Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8) and other metal composite oxides; oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5 may be used, and a carbon-based negative electrode active material such as crystalline carbon, amorphous carbon, or a carbon composite may be used alone or in combination of two or more.

[0084] The negative electrode can be manufactured by a method known in the art.

[0085] Hereinafter, examples will be given for a specific description of the present invention. However, the examples according to the present invention can be deformed into various other forms, and the scope of the present invention should not be construed as being limited to the examples described below. The examples of the present invention are provided to more fully explain the present invention to those with average knowledge in the art.

[0086] <Sulfide-based solid electrolytes used in the examples and comparative examples> In the examples and comparative examples of the present invention, an argyrodite-based solid electrolyte (manufacturer: Mitsui) was purchased and used.

[0087] Control Example 1: Measurement of ionic conductivity of sulfide-based solid electrolyte The purchased argyrodite-based solid electrolyte powder was molded into pellets at 360 MPa without being exposed to the air, and sandwiched between stainless steel electrodes to measure the ionic conductivity, which was 3.06 mS / cm.

[0088] Control Examples 2 to 4: Measurement of ionic conductivity immediately after production of sulfide-based solid electrolytes The purchased argyrodite-based solid electrolyte powder was mixed with each of the solvents in Table 1 below without being exposed to the air, and mixed at 2,000 rpm for 6 minutes, and then dried at 100° C. for 6 hours under vacuum conditions.

[0089] Each of the dried solid electrolyte powders was formed into a pellet shape and sandwiched between stainless steel electrodes to measure the ionic conductivity. The results are shown in Table 1 below.

[0090] [Table 1]

[0091] From the above experiment, it was confirmed that when a sulfide-based solid electrolyte not exposed to moisture is treated with a solvent having a dielectric constant of less than 7, there is almost no change in ionic conductivity compared to the case where no solvent treatment is performed in Control Example 1. This difference in degree is believed to be due to a decrease in ionic conductivity caused by contact with air and impurities during the solvent treatment.

[0092] Comparative Example 1: Measurement of ionic conductivity of sulfide-based solid electrolyte after storage The argyrodite-based solid electrolyte powder was exposed to the air in a dry room (H2O 100-160 ppm level) for 5 hours, and then the exposed solid electrolyte powder was molded into pellets and sandwiched between stainless steel electrodes to measure the ionic conductivity, which was 1.99 mS / cm.

[0093] As a result of the experiment, it was confirmed that the ionic conductivity was reduced by 35% compared to the electrical conductivity of Control Example 1.

[0094] Examples 1 to 3: Measurement of ionic conductivity of sulfide-based solid electrolyte after storage and solvent mixing treatment The sulfide-based solid electrolyte exposed to the air in the same manner as in Comparative Example 1 was mixed with each of the solvents in Table 2 below and mixed at 2,000 rpm for 6 minutes, and then dried at 100° C. under vacuum conditions for 6 hours.

[0095] Each of the dried solid electrolyte powders was formed into a pellet shape and sandwiched between stainless steel electrodes to measure the ionic conductivity. The results are shown in Table 2 below.

[0096] [Table 2]

[0097] From the above experiment, it can be confirmed that the ionic conductivity of the sulfide-based solid electrolyte, which had decreased due to dry room exposure (a decrease of 35%), was restored to 94% by the solvent treatment compared to the ionic conductivity of the solid electrolyte measured without dry room exposure (Control Example 1).

[0098] Example 4 and Comparative Example 2: Production of all-solid-state batteries An all-solid-state battery was manufactured using the sulfide-based solid electrolyte used in the measurement of ionic conductivity in Comparative Example 1 (Comparative Example 5).

[0099] In addition, an all-solid-state battery was manufactured using the sulfide-based solid electrolyte used in the measurement of ion conductivity in Comparative Example 1 (Comparative Example 2).

[0100] In addition, an all-solid-state battery was manufactured using the sulfide-based solid electrolyte used in the measurement of ion conductivity in Example 3 (Example 4).

[0101] (1) Manufacturing of all-solid-state electrolytes The sulfide-based solid electrolyte powder used in the measurement of ion conductivity in the Comparative Example 1, the sulfide-based solid electrolyte powder used in the measurement of ion conductivity in the Example 3, and the sulfide-based solid electrolyte powder used in the measurement of ion conductivity in the Comparative Example 1 were mixed with a rubber-based binder and a solvent xylene in a weight ratio of 55:2:43 to prepare a slurry composition. Each of the slurry compositions was coated on a release paper by a tape-cast method and then dried at a temperature of 100° C. in a vacuum state for 6 hours. Then, a pressure of 500 MPa was applied to form a solid electrolyte membrane having a thickness of 30 μm. Then, the release paper was removed, and the free-standing sulfide-based solid electrolyte membrane was applied to a cell.

[0102] (2) Manufacturing of all-solid-state batteries The sulfide-based solid electrolyte membranes prepared above were laminated in the order of a positive electrode (NCM811), a solid electrolyte membrane, and a negative electrode (Li metal), and then pressurized at a pressure of 200 MPa. Then, current collectors were bonded to the positive and negative electrodes, and the resulting laminate was assembled into an aluminum pouch cell to prepare all-solid-state batteries of Control Example 5, Example 4, and Comparative Example 2, respectively.

[0103] Experimental example 1: Evaluation of the characteristics of all-solid-state batteries The coulombic efficiency of the all-solid-state batteries of Control Example 5, Example 4, and Comparative Example 2 was compared. The life characteristics of each of the batteries of Control Example 5, Example 4, and Comparative Example 2 at 0.05 C charge and discharge were measured at 60° C. and 1 C charge and discharge to evaluate the life performance of the batteries. The results are shown in Table 3 below.

[0104] [Table 3]

[0105] As a result of the above evaluation, it was confirmed that the sulfide-based solid electrolyte in which the ionic conductivity was restored by the method of the present invention (Example 3) did not deteriorate the quality of the battery, compared with the solid electrolyte in which the ionic conductivity was not reduced (Control Example 1).

Claims

1. a) contacting a sulfide-based solid electrolyte having reduced ionic conductivity with a solvent having a dielectric constant of less than 7; and b) drying the solid electrolyte that has been in contact with the solvent.

2. The method for recovering ionic conductivity according to claim 1 , wherein the decrease in ionic conductivity in step a) is caused by exposure of the sulfide-based solid electrolyte to moisture.

3. 2. The method for recovering ionic conductivity according to claim 1, wherein the decrease in ionic conductivity in step a) is caused by exposure of the sulfide-based solid electrolyte to an atmosphere containing moisture.

4. The method for recovering ionic conductivity according to claim 1, wherein the decrease in ionic conductivity in step a) is 1% to 80% of the ionic conductivity of the sulfide-based solid electrolyte before exposure to the atmosphere, which is 100%.

5. The method for recovering ionic conductivity according to claim 1, wherein the recovery of ionic conductivity in the step a) increases the ionic conductivity of the sulfide-based solid electrolyte having reduced ionic conductivity by 1% to 300%.

6. 2. The method for recovering ionic conductivity of a solid electrolyte according to claim 1, wherein the solvent having a dielectric constant of less than 7 is at least one selected from the group consisting of xylene, isobutyl butyrate, anisole, toluene, hexane, heptane, isobutyl isobutyrate (IBIB), decane, dibutyl ether, and butyl butyrate.

7. 2. The method for recovering the ionic conductivity of a solid electrolyte according to claim 1, wherein the contact between the sulfide-based solid electrolyte and the solvent is carried out by mixing the solid electrolyte with the solvent, spraying the solvent onto the solid electrolyte, or immersing the solid electrolyte in the solvent.

8. 2. The method for recovering ionic conductivity of a solid electrolyte according to claim 1, wherein the contact between the sulfide-based solid electrolyte and the solvent is performed such that the entire surface of the sulfide-based solid electrolyte is wetted with the solvent.

9. The method for recovering the ionic conductivity of a solid electrolyte according to claim 1 , wherein the drying is performed in a vacuum atmosphere.

10. The sulfide-based solid electrolyte is Li 10 GeP 2 S 12 , Li 2 S-P 2 S 5 Glass, thio-LISICONS, Li 9.54 S 1.74 P 1.44 S 11.7 C 0.3 , Li 6 P.S. 5 X (LPSX; X = Cl, Br, I) Argyrodite, and Li 12-m-x + (M m+ Y 4 2- ) Y 2-x 2- X x - (wherein M=Si, Ge, Sn, P, As; Y=O, S, Se, Te; X=Cl, Br, I; 0≦x≦2),

11. A sulfide-based solid electrolyte whose ionic conductivity has been restored by the method according to any one of claims 1 to 10.

12. a positive electrode; a negative electrode; and a solid electrolyte interposed between the positive electrode and the negative electrode; The solid electrolyte of claim 11 .

Citation Information

Patent Citations

  • Solid electrolyte, electrochemical battery including the solid electrolyte, and method of preparing the solid electrolyte

    EP3819966A1

  • All-solid lithium secondary battery

    JP2009193727A

  • Recovery method of sulfide solid electrolyte

    JP2015018726A

  • Recovery method of sulfide solid electrolyte

    JP2015050161A

  • Composition for preventing or treating neurodegenerative diseases comprising mixture of herbal extracts of genkwae flos, clematidis radix, and gastrodiae rhizoma

    KR102310764B1